Camera movement in Martin Scorsese's films : an analysis of authorship from script to screen - Chua, Xian Jun (Universiti Malaysia Sarawak (UNIMAS), 2013)
This research applies the auteur theory to study a specific cinematic techniwue in the fils of Martin Scorsese: camera movement n the long take. Particular scenes with this type of shot in Mean Streets (1973), Goodfellas (1990), and Casino (1995) - all directed by Scorsese but using different cinematographers and writers - are analyzed to assess the true authorship of this camera movement. This research has then been applied in the production of a short film, in the same genre as the three afirementioned fils, featuring dynamic camera movement in a long take.